Economic education for the kindergarten-primary grades -- a review of the literature from 1960 through 1970 - Steinhoff, Darleen (My University, 1971)
Statement of the Problem: The purpose of this study was to review the literature from 1960 through 1970 to determine the extent to which common concepts and generalizations identified with the discipline of economics could be included in the kindergarten-primary curriculum; to discover through the literature the advantages and disadvantages of teaching economics in the kindergarten-primary grades; and to describe characteristics of some of the experimental economic programs. Methods and Procedures Used: Research at the Center for Economic Education at WSU-La Crosse and the WSU-La Crosse Library provided an abundance of valuable information on the need for economic understanding, what help is available, economics as a discipline, and economic concepts in the primary grades. The books, magazine articles, pamphlets, speeches, and reports were read. The information useful to the purpose of this study was collected, compiled, and made possible the writing of this paper. Summary of Findings: According to most authorities consulted, a reasonable level of economic understanding was considered an essential part of the equipment of every American for effective living as well as effective citizenship. The economic concepts: wants, goods, services, consumer, producer, production and resources can be understood by kindergarten-primary children as long as they are related to the maturity of the youngster. The children who are trained in economics in the kindergarten-primary grades will have advantages in solving the problems confronting society and their personal needs, in making wise choices, in deciding what is important to them, in their ability to deal with abstractions, and in their analytical ability. Economics is usually correlated with other subjects in the kindergarten-primary grades.
Keywords: Economics -- Study and teaching (Primary)